What is Islam? the importance of being Islamic - Ahmed, Shahab (Princeton University Press, 2016)
"A book that is certain to provoke debate and significantly alter our understanding of Islam, [this work] reveals how Muslims have historically conceived of and lived with Islam as norms and truths that are at once contradictory yet coherent"--Front jacket flap